Framing Good Inclusion: School Awards and Leadership Expectations in Norway and Germany - Dahle, Carolina (Nordic Journal of Comparative and International Education (NJCIE), 2025)
This comparative study explores how the idea of good inclusion is framed in Norway and Germany, and how these framings shape expectations for school leaders. The analysis draws on two sources: the criteria of national school awards for inclusive education and the ways in which leadership magazines construct expectations for school leaders. Recognizing both the importance and ambiguity of inclusion—and the uncertainties it poses for educational leadership—the study uses qualitative content analysis to examine how inclusion is defined and communicated across contexts. Award websites and leadership magazine articles were analyzed through a structured process of paraphrasing to define inductive categories. The findings show that while national framings of inclusion differ, emphasizing diagnostic and structural aspects in Germany and well-being and equity in Norway, expectations for school leaders converge. In both contexts, leadership magazines highlight the importance of systematic school development, stakeholder collaboration, and personal traits such as courage and empathy. This suggests that inclusion is increasingly embedded in general leadership ideals, positioning it as a core element of what defines a good school. This study contributes to comparative and international education research by illuminating how national framings of inclusion shape leadership expectations across contexts, offering insights into the interplay between Nordic and non-Nordic perspectives.